2021
DOI: 10.1183/23120541.00045-2021
|View full text |Cite
|
Sign up to set email alerts
|

Lung ultrasound assessment for pneumothorax following transbronchial lung cryobiopsy

Abstract: BackgroundIatrogenic pneumothorax is a common and clinically important transbronchial cryobiopsy (TBCB) complication. A study was conducted to assess the diagnostic accuracy and clinical impact of immediate postprocedure lung ultrasound for diagnosing iatrogenic pneumothorax in patients suspected of interstitial lung disease (ILD) undergoing TBCB.Study design and methodsIn patients undergoing TBCB due to suspected ILD, LUS of the anterior surface of the chest was performed immediately after the TBCB procedure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
(33 reference statements)
1
3
0
Order By: Relevance
“…Another advantage of immediate LUS is its low cost and quick bedside availability. A recent study [ 20 ] found similar results for immediate LUS following TBLC. While the authors also noted low sensitivity for LUS, they described the immediate treatment option and its clinical implications as the main benefit of immediate LUS.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Another advantage of immediate LUS is its low cost and quick bedside availability. A recent study [ 20 ] found similar results for immediate LUS following TBLC. While the authors also noted low sensitivity for LUS, they described the immediate treatment option and its clinical implications as the main benefit of immediate LUS.…”
Section: Discussionsupporting
confidence: 63%
“…Recent studies have shown high diagnostic accuracy for post-procedural LUS; immediate LUS after TBFB reached a sensitivity and specificity of 100% [ 4 ], while LUS two hours after TBFB had a sensitivity of 75–100% and a specificity of 83–93% [ 3 , 19 ]. One study [ 20 ] described a sensitivity of 21.1% and a specificity of 99.2% for immediate LUS after TBLC, while another study [ 21 ] had a sensitivity of 90% and a specificity of 94% for LUS 3 h after TBLC.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical correlation is mandatory to not harm the patient. In studies regarding post-biopsy pneumothorax control sensitivity ranges 20-100% [57][58][59], which clearly shows how operator dependent it is and raises the question of the reliable application of the method.…”
Section: Comment On Applications and Misconceptionsmentioning
confidence: 99%
“…It is also important to note that, in a large pneumothorax, a “lung point” may not be visualized, where no lung is in contact with the pleura 3 . Furthermore, the literature around the use of LUS in quantification of pneumothorax volume appears limited, with one series being in spontaneously ventilated patients and another in patients following lung biopsy 4,5 . Of note, Volpicelli et al 4 note that the best images were obtained over the midaxillary and posterior thorax, and accessing the posterior thorax in ventilated patients can be challenging.…”
mentioning
confidence: 99%